Barriers to protection: gender-related persecution and asylum in South Africa - Middleton, Julie (My University, 2009)
In 1998, South Africa became the first country to explicitly state within its refugee law that gender related persecution is a binding basis for asylum, further distinguishing South Africa as a state with outstanding legal commitments to gender equality. Creating further visibility within the law, however, is only one step in the process. How the law is implemented determines its real worth and effectiveness. This study assesses the manner in which asylum decisions are made, particularly in cases of gendered harm, questioning readily accepted and essentialised notions of women and gender. It looks at how the South African asylum system defines legitimate refugees, and the interplay of fluid interpretations of gender, culture, violence and the political within these constructions. Through interviews with officials and asylum seekers, the study identifies trends in the refugee system, and interrogates the reliance on narrow understandings of the political and personal, as well as the nature of conflict and culture.
Keywords: SDG-10: Reduced inequalities